2021
DOI: 10.3390/antiox11010078
|View full text |Cite
|
Sign up to set email alerts
|

Exploring New Kingdoms: The Role of Extracellular Vesicles in Oxi-Inflamm-Aging Related to Cardiorenal Syndrome

Abstract: The incidence of age associated chronic diseases has increased in recent years. Although several diverse causes produce these phenomena, abundant evidence shows that oxidative stress plays a central role. In recent years, numerous studies have focused on elucidating the role of oxidative stress in the development and progression of both aging and chronic diseases, opening the door to the discovery of new underlying mechanisms and signaling pathways. Among them, senolytics and senomorphics, and extracellular ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 265 publications
(318 reference statements)
0
12
0
Order By: Relevance
“…On the one hand, SASP is characterized by decreased telomerase activity. Therefore, telomere length shortens [ 56 , 57 , 58 ]; however, SIPS is independent of telomerase and is considered a reversible senescence [ 59 ]. Studies in recent years have highlighted that once cells change their phenotype and acquire senescent characteristics, regardless of inducer or stressors, SIPS cells are irreversibly growth-arrested [ 60 ].…”
Section: Extracellular Vesicles As Biomarkers In Aging and Age-associ...mentioning
confidence: 99%
“…On the one hand, SASP is characterized by decreased telomerase activity. Therefore, telomere length shortens [ 56 , 57 , 58 ]; however, SIPS is independent of telomerase and is considered a reversible senescence [ 59 ]. Studies in recent years have highlighted that once cells change their phenotype and acquire senescent characteristics, regardless of inducer or stressors, SIPS cells are irreversibly growth-arrested [ 60 ].…”
Section: Extracellular Vesicles As Biomarkers In Aging and Age-associ...mentioning
confidence: 99%
“…During the natural biological process of aging, both extrinsic and intrinsic agents can cause accumulative damage in the cells, leading to the activation of cellular senescence-related mechanisms [ 21 ]. Cellular senescence is a process where cells decrease their proliferative capacity and are no longer being able to divide, in association with unique characteristics, such as flattened and enlarged morphology, increased expression of cell cycle inhibitors and elevated senescence-associated β-galactosidase activity [ 22 ]. Notably, the excessive accumulation of senescent cells in different organs and biological systems leads to a functional decline [ 6 , 7 ].…”
Section: Cellular Senescence In Biological Aging and Age-related Diso...mentioning
confidence: 99%
“…Exosomes have been reported to be involved in the crosstalk between heart and kidney, especially in chronic heart and renal diseases. In a systematic review, Mas-Bargues et al [122] grouped different evidence demonstrating that EVs from leukocytes, platelets, and endothelial cells participate in the etiopathogenesis of cardiovascular diseases in CKD, and the regulation of the biogenesis, release, and uptake may be an effective therapeutic approach to mitigate both kidney and heart injury. EVs released from senescent cells in chronic kidney disease associated with cardiovascular disorders are also emerging biomarkers of kidney and heart dysfunction in aging [122,123] Verbree-Willemsen et al [124] showed that EVs containing cystatin C and cluster of differentiation 14 (CD14) are associated with both kidney dysfunction and HF in dyspneic patients.…”
Section: Kidney and Heart Conversation: Role Of Evsmentioning
confidence: 99%
“…In a systematic review, Mas-Bargues et al [122] grouped different evidence demonstrating that EVs from leukocytes, platelets, and endothelial cells participate in the etiopathogenesis of cardiovascular diseases in CKD, and the regulation of the biogenesis, release, and uptake may be an effective therapeutic approach to mitigate both kidney and heart injury. EVs released from senescent cells in chronic kidney disease associated with cardiovascular disorders are also emerging biomarkers of kidney and heart dysfunction in aging [122,123] Verbree-Willemsen et al [124] showed that EVs containing cystatin C and cluster of differentiation 14 (CD14) are associated with both kidney dysfunction and HF in dyspneic patients. A converse point about EVs in the kidney-heart communication was demonstrated in a MI study conducted by Gao et al [125], in which exosomes containing miRNA-1956 likely released from ischemic myocardium and kidney after MI induction may lead to activating adipose-delivery mesenchymal stem cells, which are important cells for tissue regeneration.…”
Section: Kidney and Heart Conversation: Role Of Evsmentioning
confidence: 99%